The Relationship Between Hospitalization Frequency of Acute Exacerbation of Chronic Obstructive Pulmonary Disease and Anxiety and Depression - Wen-tao, Ding; Xue-xiu, Chen; Zun-jiang, Chen; Wei, Chen; Cheng-feng, Pan; Xing-ken, Fan (Frontiers in Genetics, 2022)
Depression and anxiety are common in patients with COPD, anxiety and depression can increase the risk of hospitalization and the acute exacerbation of chronic obstructive pulmonary disease. The relationship between the frequency of hospitalization for acute exacerbation of COPD (AECOPD) and the anxiety and depression of patients is not fully understood. This study aims to analyze the relationship between the frequency of hospitalizations and anxiety and depression of acute exacerbation of chronic obstructive pulmonary disease (AECOPD). A collection of 309 AECOPD patients admitted to the emergency department in our hospital from 2019 to 2020 were divided into anxiety group A and depression group D according to the Hospital Anxiety and Depression Scale (HADS) score, and divided into A1 and D1 negative groups (≤7 Score), A2 and D2 suspicious group (8-10 points), A3 and D3 confirmed group (≥11 points), paired analysis of anxiety and depression correlation and difference, and comparison of the frequency of hospitalization in each group within 2 years. The results found that anxiety and depression were significantly positively correlated (r=0.654, P=0.000), Intra-group comparison shows that the difference between the anxiety-diagnosed and non-diagnosed groups, and the depression subgroups are statistically (P＜0.05); the comparison between the anxiety subgroup and the depression subgroup showed that there was a statistical difference between the confirmed group and the non-diagnosed group (P<0.01). In short, AECOPD anxiety is positively correlated with depression. Depression is earlier and progressively affected by hospitalization frequency. Anxiety should be prioritized in the acute phase.